"Locked-Lateral" Calcaneal Fracture-Dislocation Treated with Primary Subtalar Fusion: A Case Report. Issue 1 (January 2020) - Rider, Carson M.; Olinger, Catherine R.; Szatkowski, Jan P.; Richardson, David R.
Abstract : Case report: A 65-year-old man presented with pain in his left ankle. After a delay, he presented to the orthopaedic clinic where computed tomography scan revealed an intra-articular, locked-lateral calcaneal fracture with dislocation of the peroneal tendons. Conclusions: This combination of injuries can produce subtle signs, such as an atypical double-density sign and varus talar tilt, on plain radiographs; however, the consequences of delayed treatment can be catastrophic. Early recognition and treatment are essential to avoid chronic pain and limited function.